EDUCATIONAL SYSTEM OF NNGASU: TRADITIONS AND INNOVATIONS - Alexander N. Anisimov; Vladimir N. Bobylev; Andrey V. Yanchenko; Dmitriy L. Shchegolev; Vladimir A. Filin; Olga V. Nikulina (Высшее образование в России)
The article analyzes the stages of formation and development of the system of level and continuing education in Nizhny Novgorod State University of Architecture and Construction (NNGASU) in the context of the modernization of modern national higher school. The work shows the specifics of educational activities of NNGASU as one of the leading architectural and engineering universities in Russia. The publication summarizes the innovative experience of university education.